Effect of Maxillary Expansion on the Maxillary Arch Width in Patients with Bilateral Cleft Palate: A Review - Omar H. Alkadhi; Lamis Hejab Alotaibi; Rowaida R. Alrashoud; Mohammed Hamad Almutairi; Huda Ali Al Matar; Sreekanth Kumar Mallineni (MDPI AG, 2023)
Objectives: To perform a comprehensive review of the literature to compare the effects of slow maxillary expansion (SME) and rapid maxillary expansion (RME) on maxillary arch width in patients with bilateral cleft palate. Methods: The databases include Medline, PubMed, Cochrane (CENTRAL) and (CDSR), OpenGrey, and ClinicalTrials.gov were searched for relevant studies that met the eligibility criteria published before or on 31 October 2022. The search was confined to the English language. The selection of eligible studies and collection of data were performed independently. Risk of bias assessment was conducted using the Cochrane Risk of Bias tool 2.0. Results: Two randomized controlled trials were available based on the search in the published literature. Both studies compared arch width between SME and RME in cleft palate patients and digitals casts and three-dimensional images used for the evaluation. A moderate risk of bias was evident in the available studies. Conclusions: Both SME and RME can achieve similar amounts of maxillary expansion in patients with bilateral cleft palate.